Pengaruh Alat Semai Otomatis Berbasis Mikrokontroler Terhadap Pertumbuhan Benih Dalam Sistem Hidroponik - Palallo, Muh Mufty Maarif; Patang, Patang; Mukhlis, Andi Muhammad Akram (Agricultural Technology Education Study Program, 2024)
Seeding is one of the factors that influences plant growth. In general, sowing requires more attention because plant seeds are very sensitive to external factors such as humidity in the planting medium, environmental temperature, exposure to sunlight and pests. In this way, farmers are required to carry out direct control during the sowing process. Therefore, a system or tool is needed in the sowing process to improve the quality of the seeds produced and can reduce the time used to control the seeds during sowing. The purpose of this study was to determine the effect of using automatic seedling tools on seed growth in a hydroponic system. This type of research includes quantitative research with experimental research methods using Completely Randomized Design (CRD). The results of this study indicate that sowing using automatic seedling tools has an effect on the height of mustard greens and pakcoy plants, but has no effect on the number of leaves and root length. Seed yields that had been sown conventionally were better than seed yields on automatic seedling devices because automatic seedling experienced etiolation.